IDIOTIPE KOPI ARABIKA TANAMAN BELUM MENGHASILKAN PADA LINGKUNGAN DATARAN RENDAH DAN MENENGAH - - Alnopri; - Prasetyo; Bandi Hermawan (Universitas Trunojoyo Madura, 2011)
Coffee is the second priority and is nationally leading commodity aimed to increase export as well as to improve added values of national production in order to gain high compatibility in the international level. The development of coffee plantation in Indonesia focuses on the increased proportion of arabica coffee. The technology offered is to establish the superior characteristics of robusta coffee (lowland habitats) and that of arabica coffee (highland habitats) into a single crop named robbica cofffee. The idiotype of arabica crops has not been studied at the low and moderate altitude of land. The study uses a randomized block design arranged at a split-plot, where two altitude act as the main-plot (10 m and 500 m above sea level) and ten genotypes of arabica coffee as the sub-plot (five genotypes of arabica and five genotypes of robbica), with three replicates and four crops for each experimental unit. The sample crops are located at the centre of the plot (two crops for each experimental unit). Variables observed are plant height (cm), stem diameter (mm), are of a couple of leaf (cm2), weight of a couple of leaf (gram), the number of stomata, the level of leaf greeness, the content of leaf chlorophile (A and B), and nitrate reductase activity. Result of variance analysis showed that genotypes significantly affect plant height, stem diameter, area of a couple of leaf, weight of a couple of leaf, and the number of stomata. The level of leaf greeness, and the number of chlorophile (A and B) show insignificant responses genotypes. The study conclude that the idiotype of arabica coffee, i.e. that is having a combination of robusta and arabica performs better than pure arabica, the habitat of moderate altitude is more favourable than that lowland, and the cultivation of arabica at the moderate altitude requires a modification of enviroment by plantibg the shade plant from leguminosae family.